Synthesis and Application of 4′-C-[(N-alkyl)aminoethyl]thymidine Analogs for Optimizing Oligonucleotide Properties - Kota Fujiki; Yuri Kakisawa; Elsayed M. Mahmoud; Yoshihito Ueno (Molecules, 2025)
Gapmer-type antisense oligonucleotides (ASOs) are an emerging class of therapeutic agents that directly inhibit pathogenic mRNA. In this study, three new 4′-C-substituted thymidine analogs were generated using a synthetic strategy recently established by our group, namely, 4′-C-(N-ethyl) aminoethyl (4′-EAE-T), 4′-C-(N-butyl) aminoethyl (4′-BAE-T), and 4′-C-(N-octyl) aminoethyl (4′-OAE-T). Their properties were evaluated and compared with those of previously reported analogs, including 4′-C-aminoethyl (4′-AE-T) and 4′-C-(N-methyl) aminoethyl (4′-MAE-T). The novel nucleoside analogs were subsequently incorporated into gapmer-type ASOs featuring phosphorothioate (PS) linkages and locked nucleic acids (LNAs) in the wing regions. The incorporation of 4′-EAE-T and 4′-BAE-T analogs resulted in RNA binding affinities similar to that of the previously reported 4′-MAE-T analog, whereas a marked decrease in RNA affinity was noted for 4′-OAE-T, however, this reduction was mitigated when combined with other chemical modifications. Furthermore, the structural modifications conferred enhanced nuclease resistance under bovine serum conditions, with 4′-EAE-T resulting in the highest stability, followed by 4′-BAE-T and 4′-OAE-T. Additionally, oligonucleotides modified with the developed analogs preserved their RNase H cleavage susceptibility, albeit inducing minor alterations in the cleavage pattern. Finally, the oligonucleotides were applied in a gene silencing experiment targeting the KRAS gene, conducted without the use of transfection agents, displaying gene silencing activities comparable to that of the control, with the exception of the 4′-OAE-modified nucleotide, which exhibited low activity.